Sharing Circles as a way to facilitate capacity sharing across generations and cultures ... - Grosfeld, Lisa (Zenodo, 2023)
This presentation was part of the session "Improving intercultural and transdisciplinary collaborations in Arctic research by better understanding the value of capacity sharing - Special ECR and Arctic youth version" at the Arctic Science Summit Week 2023. In this presentation we present an approach towards starting intercultural and transdisciplinary dialogue in the frame of the EU project Arctic PASSION. The format of a Sharing Circle for early career scientists and Arctic youth will be presented and discussed. This activity was driven by the project’s principle surrounding intercultural capacity sharing. The concept of the Sharing Circle has been co-created from the beginning with early career scientists and the Indigenous community where the event will take place. Discussions held in indoor and outdoor settings will help facilitate transdisciplinary dialogue and two-way, cross-cultural knowledge sharing. It is hoped that the next generation of Arctic scientists will gain an understanding of the ... : See more information here: https://arcticpassion.eu/sharingcircle/ ...